The Use of Fluoride Varnish in Pediatric Dentistry - Anggraini, Laelia Dwi (Universitas Muhammadiyah Yogyakarta, 2025)
Fluoride Varnish is a fluoride system applied professionally to prevent caries. This material can stick to the tooth surface for a relatively long time, thereby releasing fluoride efficiently and effectively. This fluoride varnish can prevent enamel demineralization in children with moderate to high risk of caries. Below we introduce various types of fluoride varnishes that are often used in the field of pediatric dentistry. This article is about the review of fluoride varnish in the world of pediatric dentistry, based on 39 journal references, consisting of 6 journals on fluoride in pediatric dentistry, 9 fluoride varnish, 6 oral health, 3 dental caries, 3 water fluoridation, 2 topical applications of flour, 5 preventions in dentistry, 2 fluoride mouthrinses, 1 fluoride gel, 2 materials in dentistry. Based on the literature review above, it can be concluded that the use of fluoride varnish in pediatric dentistry includes several important aspects. Fluoride varnish has been proven effective in preventing dental caries in children. Its regular application can reduce the incidence of caries, especially in teeth that are susceptible to damage. The fluoride varnish application process is easy and painless, making it very suitable for use in children. This product is also safe if used according to established guidelines. Fluoride varnish can provide long-term protection against tooth decay. This is an important part of a comprehensive caries prevention program. The use of fluoride varnish also supports public health efforts by reducing the prevalence of caries in the pediatric population, especially in groups at high risk for caries. Fluoride varnish is generally well accepted by children compared to other caries prevention methods because its application is quick and easy. Conclusion. Overall, fluoride varnish is an important tool in the strategy of preventing dental caries in children, offering effective, safe, and well-accepted protection.